2022
DOI: 10.3389/fphar.2021.803304
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress of RGD Modified Liposomes as Multistage Rocket Against Cancer

Abstract: Cancer is a life-threatening disease, contributing approximately 9.4 million deaths worldwide. To address this challenge, scientific researchers have investigated molecules that could act as speed-breakers for cancer. As an abiotic drug delivery system, liposomes can hold both hydrophilic and lipophilic drugs, which promote a controlled release, accumulate in the tumor microenvironment, and achieve elongated half-life with an enhanced safety profile. To further improve the safety and impair the off-target effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 152 publications
(144 reference statements)
0
30
0
Order By: Relevance
“…We included peptides specific for surface receptors known to be expressed on RMS cells (NCAM-1, EGFR, CB1, TFR1, and uPAR; see Supplementary Table S2 for an overview of the literature), or reported to successfully target other tumors, tumor blood vessels, or tumor lymphatic vessels (Nucleolin, CD13, p32). We also included integrin α v β 3 -targeting peptides (CRGDS, cRGDyK) since integrin α v β 3 is one of the most investigated targets [ 21 , 22 ] and we previously showed successful RMS-targeting with RGD-based peptides [ 23 , 24 ] ( Table 1 ). Expression of the targeted receptor was additionally verified by analysis of publicly available expression data ( Supplementary Figures S1–S3 ).…”
Section: Resultsmentioning
confidence: 99%
“…We included peptides specific for surface receptors known to be expressed on RMS cells (NCAM-1, EGFR, CB1, TFR1, and uPAR; see Supplementary Table S2 for an overview of the literature), or reported to successfully target other tumors, tumor blood vessels, or tumor lymphatic vessels (Nucleolin, CD13, p32). We also included integrin α v β 3 -targeting peptides (CRGDS, cRGDyK) since integrin α v β 3 is one of the most investigated targets [ 21 , 22 ] and we previously showed successful RMS-targeting with RGD-based peptides [ 23 , 24 ] ( Table 1 ). Expression of the targeted receptor was additionally verified by analysis of publicly available expression data ( Supplementary Figures S1–S3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Cyclic RGD is among the most widely studied targeting ligand and it has demonstrated strong affinities for α v β 3 integrin, a key receptor expressed by multiple cell populations including among others, cancer cells of the skin and of the breast, endothelial cells, and neutrophils. Surface functionalization of nanoparticles with targeting ligands such as cRGD has shown significant advantages in preclinical cancer nanotherapy studies [51,52].…”
Section: Identifying the Optimal Crgd Decoration Density For Follow-u...mentioning
confidence: 99%
“…Cyclic RGD is among the most widely studied targeting ligand and it has demonstrated strong a nities for α v β 3 integrin, a key receptor expressed by multiple cell populations including among others, cancer cells of the skin and of the breast, endothelial cells and neutrophils. Surface functionalization of nanoparticles with targeting ligands such as cRGD has shown signi cant advantages in preclinical cancer nanotherapy studies [49,50]. However, in-depth cellular examination already revealed that RGDtargeting induced nanoparticle association with tumor vasculature while marginally reaching the tumor interstitium [29,51].…”
Section: Identifying the Optimal Crgd Decoration Density For Follow-u...mentioning
confidence: 99%